Microstructural evolution of W-10Re alloys due to thermal cycling at high temperatures and its impact on surface degradation. (November 2020) - Siller, M.; Schatte, J.; Gerzoskovitz, S.; Knabl, W.; Pippan, R.; Clemens, H.; Maier-Kiener, V.
Abstract: This paper features four microstructurally different tungsten 10 wt% rhenium (W10Re) alloys tested by thermal cycling at high temperatures in a conventional electron beam welding machine. The sample surfaces undergo minimum temperatures of 1700–1750 °C with 3.000–180.000 additional temperature jumps of 170–200 °C. The used materials show microstructural changes as well as surface damage related to the exposure time and the number of applied temperature jumps. The loaded surfaces show formation of slip bands, grain boundary bulging, pitting, thermal grooving as well as crack formation after the cyclic thermal loading. An initial columnar grain structure reduced pitting of grains at the surface by influencing the preferential crack direction, while on the other hand increasing surface swelling. Introducing HfC into the W10Re matrix led to a smaller final grain size after recrystallization as well as decreasing surface swelling and pitting. A larger initial grain size has shown increased surface degradation and large amounts of swelling. The changes in microstructure were characterized by classical metallographic means including light optical microscopy and hardness testing. The surface damage was investigated in detail by using laser scanning microscopy. Differences in surface damage mechanisms were characterized by electron back scatter diffraction and scanning electron images. The combination of temperature measurements with finite element modeling enabled to calculate the temperatures and loading conditions of the samples. Graphical abstract: Unlabelled Image Highlights: Four microstructurally different tungsten-rhenium alloys were subjected to cyclic heat loading by electron beam exposure. The samples recrystallized during the exposure and showed both material and load-dependent surface damage. Surface damage consisted of cracks along grain boundaries, pitting, swelling and the formation of slip bands. The crack orientation distribution was strongly influenced by the initial microstructure before recrystallization.